Takhrij and Syarah Hadith of Agrotechnology Study of Black Cumin Plants as Medicine - Daffa Muhammad Rizky; Efrin Firmansyah; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith regarding black cumin plants. This research method is a qualitative type through literature and field studies with the takhrij and syarah hadith approaches. The results and discussion of this research is that black cumin is an antidote for all diseases according to the hadith of the Prophet SAW with a lot of ingredients in it. The conclusion of this research is takhrij and syarah hadith about black cumin with agrotechnology analysis found as an antidote for every disease except death.